Analysis of secondary flow characteristics and hydrodynamic instability in fluid flow through curved ducts - Chandratilleke, Tilak; Nadim, Nima; Narayanaswamy, Ramesh (HEFAT, 2011)
This paper presents an investigation on the unique flow characteristics associated with fluid flow through curved ducts, which are fundamentally different to those in straight fluid passages. In curved ducts, the flow is subjected to centrifugal forces that induce counter-rotating vortices in the main axial fluid stream and give rise to spiralling fluid motion, commonly known as secondary flow. The study develops a novel three-dimensional computational fluid dynamics analysis whereby the laminar developing fluid flow in a curved rectangular duct is modelled. The flow characteristics are identified for a range of flow rates and duct aspect ratios at several duct curvatures. The contours of secondary flow and axial velocities are obtained to recognise the influence of flow/geometrical parameters on the secondary flow. Comparisons are made between the numerical predictions and the available experimental data. It is observed that, with increased duct flow rate, the secondary flow intensifies and beyond a certain critical flow condition, leads to hydrodynamic instability. The fluid flow structure is then significantly altered with the appearance of additional pair (or pairs) of vortices, termed as Dean Vortices, at the outer wall of the curved duct. This flow behaviour is also highly influenced by the duct aspect (height to width) ratio. The paper develops and presents a new approach for predicting the onset of Dean vortex generation.